The pervasive effects of family on entrepreneurship: toward a family embeddedness perspective - Aldrich, Howard E; Cliff, Jennifer E (Journal of Business Venturing, 2003)
Families and businesses have often been treated as naturally separate institutions, whereas we argue that they are inextricably intertwined. Long-term changes in family composition and in the roles and relations of family members have produced families in North America that are growing smaller and losing many of their previous role relationships. Such transformations in the institution of the family have implications for the emergence of new business opportunities, opportunity recognition, business start-up decisions, and the resource mobilization process. We suggest that entrepreneurship scholars would benefit from a family embeddedness perspective on new venture creation.